2015
DOI: 10.1111/jcmm.12715
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic mesenchymal cells from pre‐eclamptic placentae maintain immunomodulatory features as healthy controls

Abstract: Pre‐eclampsia (PE) is one of the most severe syndromes in human pregnancy, and the underlying mechanisms of PE have yet to be determined. Pre‐eclampsia is characterized by the alteration of the immune system's activation status, an increase in inflammatory Th1/Th17/APC cells, and a decrease in Th2/Treg subsets/cytokines. Moreover, inflammatory infiltrates have been detected in the amniotic membranes of pre‐eclamptic placentae, and to this date limited data are available regarding the role of amniotic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 62 publications
4
47
0
Order By: Relevance
“…Higher expression of PD-L2 is observed in human amniotic mesenchymal stromal cells (hAMSCs) from preeclampsia patients than in hAMSCs from normal pregnant women, but conversely, these cells participate in offsetting the inflammatory environment that characterizes preeclampsia. In vitro experiments have shown that elevated PD-L2 levels in hAMSCs are associated with inhibition of CD4 + /CD8 + T-cell proliferation by suppressing Th1/Th2/Th17 polarization, inducing Tregs, blocking DCs, and switching M1 to M2 differentiation (66). To summarize, B7-DC is expressed on multiple cells and fluctuates during different pregnancy phases.…”
Section: B7-h1 and B7-dcmentioning
confidence: 99%
“…Higher expression of PD-L2 is observed in human amniotic mesenchymal stromal cells (hAMSCs) from preeclampsia patients than in hAMSCs from normal pregnant women, but conversely, these cells participate in offsetting the inflammatory environment that characterizes preeclampsia. In vitro experiments have shown that elevated PD-L2 levels in hAMSCs are associated with inhibition of CD4 + /CD8 + T-cell proliferation by suppressing Th1/Th2/Th17 polarization, inducing Tregs, blocking DCs, and switching M1 to M2 differentiation (66). To summarize, B7-DC is expressed on multiple cells and fluctuates during different pregnancy phases.…”
Section: B7-h1 and B7-dcmentioning
confidence: 99%
“…14 Amniotic cells and their secreted factors possess in vitro and in vivo immune-modulatory properties. They inhibit T-cell proliferation, [15][16][17][18] reduce the production of proinflammatory cytokines, 6,7,18,19 block the differentiation/maturation of monocytes into dendritic cells, [20][21][22] promote macrophage polarization toward an M2 anti-inflammatory phenotype, 8,23,24 induce regulatory T cells, 18,25,26 and reduce natural killer cytotoxicity. 27 However, to the best of our knowledge, no studies investigated the crosstalk between hAMSCs and immune cell populations that are involved in bleomycin-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these features, in different preclinical inflammatory disease models, hAMSCs and their conditioned medium (CM-hAMSC) have been successfully exploited, including for lung [11][12][13][14] and liver fibrosis [15], wound healing [16][17][18], collagen-induced arthritis [19,20], multiple sclerosis [19], inflammatory bowel disease, colitis [21], sepsis [19], traumatic brain injury [22], and Huntington's disease [23]. Accordingly, in vitro, we and others have demonstrated that hAMSCs and CM-hAMSC suppress the proliferation, inflammatory cytokine production, and functions of T lymphocytes [24,25], monocytes [18], dendritic cells [26], macrophages [18], and natural killer cells [27], while inducing a phenotype and functional switch of monocytes toward macrophages with anti-inflammatory pro-regenerative M2-like features [18,25], supporting the expansions of regulatory T cells [24,25].…”
Section: Introductionmentioning
confidence: 99%